Digital dermatitis in feedlot steers: description of two outbreaks in Northwestern Argentina - Juan F. Micheloud; Luis Colque Caro; Gabriel Arguello; Juan Roques; Fernando Delgado (FAVE Sección Ciencias Veterinarias, 2018)
Digital Dermatitis (DD) is a podal condition of worldwide distribution. Like other diseases that affect the bovine foot, it induces obvious lameness, with consequent productive and economic losses. It is commonly described in dairy cattle and descriptions in beef cattle are scarce. In this paper, two DD outbreaks are described in steers from feed-lot in the Argentine Northwest. Emphasis is given to more relevant aspects of clinical, epidemiological, pathological and diagnostic findings. The incidence was 5 and 35%. Lesions are typically identified in the palmar area of ​​the hind limbs, and a necrotizing dermatitis with neutrophil infiltrate was observed histopathologically. By Warthin-Starry staining was identified an intralesional spirochetes in 50% (4/8) of collected samples.